Aerodynamics in luge - Measurement and modelling - Bürger, P.; Kühne, A.; Edelmann-Nusser, J.; Krüger, A.; Ganter, N.; Link, D. (World Congress of Performance Analysis of Sport VIII, 2008)
First of all it needs to be mentioned that there is maybe not the one most advantageous posture. Depending on the athlete`s constitution and condition one might prefer an absolutely straight posture whereas another athlete can cope better with the tracks unevenness through a more relaxed position. The options for different postures appeared to be close to established positions that are nowadays used in world cup level. The optimal head position every athlete tries to achieve is "low" meaning the head being held in a straight line behind the shoulders. As this inhibits to see the track in front it can be assumed that even most elite performers glimpse right before a turn to appraise ones own position. Therefore a model offers the opportunity to predict the influence of a varying head position and accordingly other body parts not just along certain sections but also for certain sequences of time. This will estimate its extent and give a foundation for comparison on the bases of time or path.